Investigation and prosecution following workplace fatalities: Responding to the needs of families. (June 2014) - Matthews, Lynda R; Fitzpatrick, Scott J; Bohle, Philip; Quinlan, Michael
Every year, there are over 200 traumatic deaths at work in Australia. A government safety inspector usually investigates each incident. The investigation may lead to prosecution of the employer or another party deemed to have breached relevant legislation. However, little systematic research has examined the needs and interests of grieving families in this process. Drawing on interviews with 48 representatives of institutions that deal with deaths at work (including regulators, unions, employers, police and coronial officers), this article examines how they view the problems and experiences of families. Notwithstanding some recent improvements, findings indicate ongoing shortcomings in meeting the needs of families regarding information provision, involvement and securing justice.